2021
DOI: 10.31616/asj.2020.0083
|View full text |Cite
|
Sign up to set email alerts
|

Contraindication of Minimally Invasive Lateral Interbody Fusion for Percutaneous Reduction of Degenerative Spondylolisthesis: A New Radiographic Indicator of Bony Lateral Recess Stenosis Using I Line

Abstract: This study aimed to evaluate aggravated lateral recess stenosis and clarify the indirect decompression threshold by combined lateral interbody fusion and percutaneous pedicle screw fixation (LIF/PPS). Overview of Literature: No previous reports have described an effective radiographic indicator for determining the surgical indication for LIF/PPS. Methods: A retrospective review of 185 consecutive patients, who underwent 1-or 2-level lumbar fusion surgery for degenerative spondylolisthesis (DS). According to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Because instrumentation failure is the result of a complex combination of factors, the reduction maneuver itself may go unrecognized as a possible cause. This study showed a comparable or superior slip reduction rate to those reported in previous studies 3,[18][19][20][21][22][23][24] . (Table 3) One reason for the favorable results may be that the preoperative vertebral slip, which was identified as a factor contributing to the slip reduction rate in this study, was not as large as in other Spine Surgery and Related Research J-STAGE Advance Publication (February 10, 2022) Ⓒ The Japanese Society for Spine Surgery and Related Research.…”
Section: Discussionsupporting
confidence: 85%
“…Because instrumentation failure is the result of a complex combination of factors, the reduction maneuver itself may go unrecognized as a possible cause. This study showed a comparable or superior slip reduction rate to those reported in previous studies 3,[18][19][20][21][22][23][24] . (Table 3) One reason for the favorable results may be that the preoperative vertebral slip, which was identified as a factor contributing to the slip reduction rate in this study, was not as large as in other Spine Surgery and Related Research J-STAGE Advance Publication (February 10, 2022) Ⓒ The Japanese Society for Spine Surgery and Related Research.…”
Section: Discussionsupporting
confidence: 85%
“…To some extent, these can relieve the patient's symptoms in OLIF [23]. However, sometimes OLIF alone had no improvement of neurologic symptoms due to the inadequate decompression such as extreme severe lumbar canal stenosis and bony lateral recess stenosis [10,12,[24][25][26][27]. When the segment is too rigid to be restored, it is difficult to obtain a greater postoperative disc height and more indirect decompression effect [28].…”
Section: Discussionmentioning
confidence: 99%
“…The segment is too rigid to be restored, which indicates that it is difficult to obtain a greater postoperative disc height and more indirect decompression effect (24). Some studies showed that bony lateral recess stenosis is an independent predictor for failure to achieve adequate spinal decompression via indirect decompression with lateral lumbar interbody fusion (25)(26)(27). Additionally, the free herniated disc migrating into spinal canal or head, or tail of the involved segment could not be treated by indirect decompression of OLIF.…”
Section: Discussionmentioning
confidence: 99%